2022
DOI: 10.1073/pnas.2201195119
|View full text |Cite
|
Sign up to set email alerts
|

Processing of a plant peptide hormone precursor facilitated by posttranslational tyrosine sulfation

Abstract: Most peptide hormones and growth factors are matured from larger inactive precursor proteins by proteolytic processing and further posttranslational modification. Whether or how posttranslational modifications contribute to peptide bioactivity is still largely unknown. We address this question here for TWS1 (Twisted Seed 1), a peptide regulator of embryonic cuticle formation in Arabidopsis thaliana . Using synthetic peptides encompassing the N- and C-terminal processing sites and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…As previously reported for other cell wall proteins, the pattern of proline hydroxylation is variable (Duruflé et al, 2017). It has been assumed that this variability could contribute to the regulation of the biological activity or play a role in recognition of the cleavage site(s) targeted by the endoproteases as Royek et al (2022) demonstrated with tyrosine sulfation. At this point, our data did not allow addressing the question of the O-glycosylation of the hydroxyproline residues as reported for a few CLE peptides Matsubayashi, 2010, 2013;Araya et al, 2014;Takahashi et al, 2018) and PSY1 (Amano et al, 2007).…”
Section: Two Distinct Hydroxylated Scoop10 Peptides Are Present In Th...mentioning
confidence: 74%
See 1 more Smart Citation
“…As previously reported for other cell wall proteins, the pattern of proline hydroxylation is variable (Duruflé et al, 2017). It has been assumed that this variability could contribute to the regulation of the biological activity or play a role in recognition of the cleavage site(s) targeted by the endoproteases as Royek et al (2022) demonstrated with tyrosine sulfation. At this point, our data did not allow addressing the question of the O-glycosylation of the hydroxyproline residues as reported for a few CLE peptides Matsubayashi, 2010, 2013;Araya et al, 2014;Takahashi et al, 2018) and PSY1 (Amano et al, 2007).…”
Section: Two Distinct Hydroxylated Scoop10 Peptides Are Present In Th...mentioning
confidence: 74%
“…As previously reported for other cell wall proteins, the pattern of proline hydroxylation is variable (Duruflé et al ., 2017). It has been assumed that this variability could contribute to the regulation of the biological activity or play a role in recognition of the cleavage site(s) targeted by the endoproteases as Royek et al . (2022) demonstrated with tyrosine sulfation.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported for other cell wall proteins, the pattern of proline hydroxylation is variable [34]. It has been assumed that this variability could contribute to the regulation of biological activity or play a role in recognition of the cleavage site(s) targeted by the endoproteases, as Royek et al [35] demonstrated with tyrosine sulphation. At this point, our data did not allow us to address the question of the O-glycosylation of the hydroxyproline residues, as reported for a few CLE peptides [36][37][38] and PSY1 [39].…”
Section: Two Distinct Hydroxylated Scoop10 Peptides Are Present In Th...mentioning
confidence: 75%
“…Bioactivity of PSK depends on processing by SBT3.8 and Phyt2 in tomato and Arabidopsis, respectively , and on TPST for receptor recognition (Wang et al, 2015). In case of TWISTED SEED1 (TWS1), tyrosine sulfation is required for both, receptor binding and processing by SBT1.8 (Royek et al, 2022; In this work we show that anthocyanin accumulation in Arabidopsis is regulated by CLEL6. We further show that this regulatory function of CLEL6 depends on proteolytic processing by SBT6.1, tyrosine sulfation by TPST, and perception by RGF1 107 INSENSITIVE (RGI) receptors.…”
Section: Introductionmentioning
confidence: 74%
“…Bioactivity of PSK depends on processing by SBT3.8 and Phyt2 in tomato and Arabidopsis, respectively (Stührwohldt et al, 2021; Reichardt et al, 2020), and on TPST for receptor recognition (Wang et al, 2015). In case of TWISTED SEED1 (TWS1), tyrosine sulfation is required for both, receptor binding and processing by SBT1.8 (Royek et al, 2022; Doll et al, 2020; Stintzi and Schaller, 2022)…”
Section: Introductionmentioning
confidence: 99%